PLM adoption in SMEs context. Issue 5 (2nd September 2016) - Messaadia, Mourad; Baudry, David; Louis, Anne; Mahdikhah, Sara; Evans, Richard; Gao, James; Paquet, Thierry; Sahnoun, M'hammed; Mazari, Belhacène
ABSTRACT: The increasing market needs and technologies evolution, push companies to develop competitive advantages based on adequate and intensive use of information technology and communication (ICT). However, SMEs do not realize the importance of ICT adoption, which becomes vital for the development, and are not always well equipped to adopt and integrate them to their activities. The paper focused on issues regarding the ICT adoption, especially PLM solutions by SMEs. By analyzing the PLM definitions and works done, we explored indicators that impact positively or negatively ICT and PLM adoption. This paper proposes a model, currently theoretical, with empirical validation proposal through a survey. GRAPHICAL ABSTRACT: